Pemanfaatan Aplikasi Microsoft Excel Untuk Membantu Mempermudah Dalam Mengkoreksi Hasil Ujian Siswa Di SDS Alwasliyah 26 Kp.Bahari - Ummi, Khairul; Tanjung, Dahriyani Hakim; Amri, Aulia; Rahmad, Iwan Fitrianto (LPPM Universitas Potensi Utama, 2024)
Being a teacher will of course often be involved in evaluating students. This is done as a reference to see to what extent the students understand the material that has been presented by the teacher. When conducting evaluations, teachers usually have difficulty processing or correcting answers that have been done by their students. Moreover, with a large number of students, of course it will take up a lot of time if done manually. For this reason, a tool is needed that can help with the performance of teachers. The aim of this research is to provide knowledge and direct training for teachers at SDS Alwasliyah 26 Kp.Bahari. starting from designing the display, inputting student data and answer results as well as knowing the formulas needed for direct calculation of the grades obtained from the students' final exam results. From the results of the training carried out, the teachers were very enthusiastic about following it both in explaining the material until the training was carried out so that teachers were able to use Microsoft Excel to process data both to correct exam results and student grades at SDS Alwasliyah 26 Kp.Bahari. This allows for more accurate and efficient data processing, resulting in better outcomes for students..